A Case Study in Horizontal Military Innovation: The German Army, 1916-1918 - Foley, Robert T. (Journal of strategic studies, 2012)
Using the German Army from 1916 to 1918 as a case study, this article demonstrates a different form of military innovation than has hitherto been analysed by literature on the subject. During World War I, the German Army innovated by spreading knowledge between units rather than up and downthe chain of command. Thus, this army used 'horizontal innovation', rather than vertical innovation to change how it fought in the midst of battle. Although combat in World War I is significantly different from operations today, horizontal innovation offers armed forces a means by which to transform themselves much more rapidly than the traditionally recognised forms of military innovation.